Pleiotropic actions of Vitamin D in composite musculoskeletal trauma. Issue 10 (October 2020) - Valerio, Michael S.; Janakiram, Naveena B.; Goldman, Stephen M.; Dearth, Christopher L.
Highlights: CTI's are severe, multi-system injuries that impair wound healing via exaggerated and prolonged inflammation often leading to limb amputation. CTI wound healing impairments may be further complicated by pre-existing or post-injury-induced deficiencies such as vitamin D deficiency. Vitamin D's primary role in CTI healing may be regulation of inflammation, thereby promoting normative musculoskeletal tissue regeneration. Abstract: Composite tissue injuries are the result of high energy impacts caused by motor vehicle accidents, gunshot wounds or blasts. These are highly traumatic injuries characterized by wide-spread, penetrating wounds affecting the entire musculoskeletal system, and are generally defined by frank volumetric muscle loss with concomitant segmental bone defects. At the tissue level, the breadth of damage to multiple tissue systems, and potential for infection from penetration, have been shown to lead to an exaggerated, often chronic inflammatory response with subsequent dysregulation of normal musculoskeletal healing mechanisms. Aside from the direct effects of inflammation on myogenesis and osteogenesis, frank muscle loss has been shown to directly impair fracture union and ultimately contribute to failed wound regeneration. Care for these injuries requires extensive surgical intervention and acute care strategies. However, often these interventions do not adequately mitigate inflammation or promote proper musculoskeletal injury repair and force amputation of the limb. Therefore, identification of factors that can promote tissue regeneration and mitigate inflammation could be key to restoring wound healing after composite tissue injury. One such factor that may directly affect both inflammation and tissue regeneration in response to these multi-tissue injuries may be Vitamin D. Beyond traditional roles, the pleiotropic and localized actions of Vitamin D are increasingly being recognized in most aspects of wound healing in complex tissue injuries – e.g., regulation of inflammation, myogenesis, fracture callus mineralization and remodeling. Conversely, pre-existing Vitamin D deficiency leads to musculoskeletal dysfunction, increased fracture risk or fracture non-unions, decreased strength/function and reduced capacity to heal wounds through increased inflammation. This Vitamin D deficient state requires acute supplementation in order to quickly restore circulating levels to an optimal level, thereby facilitating a robust wound healing response. Herein, the purpose of this review is to address the roles and critical functions of Vitamin D throughout the wound healing process. Findings from this review suggest that careful monitoring and/or supplementation of Vitamin D may be critical for wound regeneration in composite tissue injuries.